Image contrast enhancement based on Hessian matrix - Eng, Kian Kiat (Nanyang Technological University, 2023)
Image enhancement is the process by which parts of the image that are not clear due to bad illumination or blurred due to motion etc. can be made visually perceptible. In this paper, we will look into a histogram-based method for image enhancement where the histogram is weighted by a Hessian matrix. The role of the Hessian matrix is to identify regions in an image that are smooth and therefore need to be enhanced as opposed to textured regions whose contrast is retained.